A COMPARISON OF NEGOTIATIONS IN BOSNIA AND HERZEGOVINA, KOSOVO AND MACEDONIA – DIFFERENCES AND SIMILARITIES IN THE NEGOTIATION PROCES AND THE IMPLEMENTATION OF PEACE AGREEMENTS - Sherifi, Qazime (KNOWLEDGE - International Journal, 2025)
This paper analyzes and compares the negotiations and the effectiveness of preventive diplomacy in three conflicts of the former Yugoslavia: in Bosnia and Herzegovina, Kosovo, and Macedonia. In each case, it evaluates the role of international actors in crisis management and conflict resolution. While Bosnia and Kosovo involve major international interventions and intensive diplomatic mediation, Macedonia presents a successful case of preventive diplomacy. The study highlights the differences in strategies employed by international actors, as well as their influence on the final peace outcomes. Using a comparative approach and analysis of key documents, the paper aims to contribute to the understanding of factors that shape the effectiveness of negotiations in different political and ethnic contexts.